The Co-Construction of Participation Through Oral Mediation in the EFL Classroom (2016)
Sociocultural theory argues that an individual’s mental, social, and material activity is mediated by cultural tools. One such tool is the language or discourse teachers use during whole class interaction in the second language classroom. The purpose of this study was to examine how a Colombian se-cond language teacher mediated her ninth-grade students’ participation during classroom interaction. We videotaped and transcribed five lessons and interviewed the teacher after each lesson. Findings revealed that the teacher mainly used questions, elaborations, recasts, and continuatives in patterned combinations to help learners co-construct relevant content and sustained participation. Such mediation provided learners with frequent affordances to engage in meaning-making, a necessary condition for developing a new language.